2016
DOI: 10.21013/jas.v4.n2.p2
|View full text |Cite
|
Sign up to set email alerts
|

Response of Golden Acre Cabbage to Foliar Application of Water Soluble Fertilizers on Plant Growth and Seed Yield

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
1
1
Order By: Relevance
“…The control or foliar combined with Cypermetrine recording least yields of 10 and 9 tonnes/ha respectively could be that the foliar application of fertilizer had no effect on the yield of cabbage. This disagrees with Narayan et al, (2016) who reported of maximum seed yield of cabbage (10.37 q/h) with the foliar application of NP2O5K2O (15-15-30) against the minimum seed yield (5.50 q/h) in untreated plots. The authors further attested that the spraying of Water Soluble Fertilizers (WSF) leads to proper development of flower buds and seed setting of cabbage which ultimately improves the seed yield.…”
Section: Effect Of Soil Amendment On Yield Componentscontrasting
confidence: 99%
“…The control or foliar combined with Cypermetrine recording least yields of 10 and 9 tonnes/ha respectively could be that the foliar application of fertilizer had no effect on the yield of cabbage. This disagrees with Narayan et al, (2016) who reported of maximum seed yield of cabbage (10.37 q/h) with the foliar application of NP2O5K2O (15-15-30) against the minimum seed yield (5.50 q/h) in untreated plots. The authors further attested that the spraying of Water Soluble Fertilizers (WSF) leads to proper development of flower buds and seed setting of cabbage which ultimately improves the seed yield.…”
Section: Effect Of Soil Amendment On Yield Componentscontrasting
confidence: 99%
“…Moyin-Jesu1 (2015) reported that the application of NPK 15-15-15 fertilizer significantly increased the cabbage head yield and growth parameters compared to control. Foliar applications of cabbage with NPK at different ratios increased plant height, number of branches compared to control and head yield (Atanasova et al , 2007 andNarayan et al , 2016) Traditionally, amino acids were used as precursors and protein constituents. Many amino acids often serve as precursors to other compounded nitrogen, e.g., nucleic acids.…”
Section: Introductionmentioning
confidence: 99%